New engineering approach for the development and demonstration of a multi-purpose platform for the Blue Growth Economy - Lagasco, F.; Collu, M.; Mariotti, A.; Safier, E.; Arena, F.; Atack, T.; Brizzi, G.; Tett, P.; Santoro, A.; Bourdier, S.; Salcedo, F. F.; Muggiasca, S.; et al. (Volume 6: Ocean Space Utilization, 2019)
Aquaculture is currently the fastest growing food sector in the world and the open oceans are seen as one of the most likely areas for large scale expansion [1], [2], [3]. The global demand for seafood is continuing to rise sharply, driven by both population growth and increased per capita consumption, whilst wild capture fisheries are constrained in their potential to produce more seafood. A recently funded EC project, the Blue Growth Farm BGF (GA n. 774426, 1st June 2018 ÷ 30th September 2021) aims at contributing to this world need with an original solution. The Blue Growth Farm proposes an efficient, cost competitive and environmentally friendly multi purpose offshore farm concept based on a modular floating structure, moored to the seabed, meeting requirements of efficiency, cost-competitiveness and environmental friendless, where automated aquaculture and renewable energy production systems are integrated and engineered for profitable applications in the open sea. In the present paper, the overall engineering approach developed to carry out the research work is presented, described and justified. Different technical and scientific challenges are addressed through an integrated industrial engineering design approach, where all disciplines are tuned to achieve the Blue Growth Farm main targets, represented by: i) guaranteeing expected nominal fish production thanks to advanced automation and remote control capabilities; ii) minimizing the pollution introduced at marine ecosystem level when exploiting the marine natural resources, whilst increasing the social acceptance and users community agreement; iii) maximizing the electricity production in the Blue Growth Farm potential installation area ecosystem to provide energy supply to the on board electrical equipment and to dispatch the extra produced electric energy to the land network. Preliminary engineering design results are promising to demonstrate effective increase of safety and efficiency by reducing on board human effort and consequently risks at ...